Developing Supplementary Materials for Reading Skill by Using Local Wisdom - Yayu Anggraini H. Katili (English Department of Faculty of Tarbiyah and Teacher Training, 2023)
The purposes of this study are to describe the students’ needs and to design the supplementary materials for reading skill by using local wisdom for second grade students of MTs Al Khairaat Gorontalo. By using Research and Development Method, the results of this study show that 1) students need materials which were related to decription of tourism objects, warning about cleanliness and the local story. 2) Students preffer to read text which consisted of 200-300 words. 3) Students want to answer 5 W + 1 H questions and True False questions in reading activities. 4) Students want to match the vocabularies with the pictures in vocabulary building activity. 5) Students want to fill in the blank sentences in Grammar activity. 6) Students want to work in group and the teacher should help them when they had a problem in the classroom. The content of the materials should be developed in interesting and easy way, language used must be appropriate with the students’ language level, build cultural awareness and motivated students to read. Therefore, by integrating local wisdom into supplementary reading materials, the students and the teacher feel easy and motivated in teaching and learning process.